A systematic review: identifying research gaps in emotional intelligence development using storybook as a learning tool - Isha, Siti Rahayu; Azam, Mohamad Naqiuddin Dahamat; Daud, Mohd Najmi (Human Resource Management Academic Research Society, 2022)
Emotional Intelligence is defined by its capacity for social success. Children must have the ability to properly assess other individuals or groups and react in an acceptable way. This systematic review intends to fill the knowledge gap on the usage of storybooks as a learning tool for developing emotional intelligence among preschool children. According to the findings, there has been little research into the significance of storybooks as a learning tool for developing emotional intelligence. Furthermore, most of the studies do not use preschool children as a sample. As a result, many of the studies concentrated on the effects on a few emotions, which cannot be considered a true definition of emotional intelligence. According to the findings, more research is needed to determine the benefits of storybooks as a learning tool in developing emotional intelligence in children. Aside from that, findings have revealed the importance of creating emotional intelligence-themed children's storybooks as a learning tool for the development of emotional intelligence in children.